Transcranial direct current stimulation in stroke – Motor excitability and motor function. (December 2022) - Yasaroglu, Sinan; Liepert, Joachim
Highlights: Anodal transcranial direct current stimulation is associated with a cortical disinhibtion in subacute stroke patients. The degree of cortical disinhibition correlates with motor performance. Cathodal transcranial direct current stimulation of the affected hemisphere did not modulate motor excitability. Abstract: Objective: To characterize motor excitability changes and changes of motor performance induced by a single anodal and cathodal transcranial direct current stimulation (tDCS) session in stroke patients. Methods: Twenty subacute stroke patients participated. Motor performance was tested with the Box and Block Test [BBT]. Motor cortex excitability (short interval intracortical inhibition [SICI], intracortical facilitation [ICF], long interval intracortical inhibition [LICI]) was examined by paired pulse transcranial magnetic stimulation before and after a single tDCS session (20 minutes, 1, 0 mA). On two different occasions, patients received anodal and cathodal tDCS over the affected hemisphere. TMS recordings were taken from both hands consecutively. Results: Anodal tDCS significantly reduced SICI without changing ICF or LICI. Cathodal tDCS did not change motor excitability. Both types of tDCS did not alter motor performance. Even prior to anodal tDCS, SICI in the affected hemisphere was lower than in the unaffected hemisphere and was correlated with BBT changes after anodal tDCS. Conclusions: Anodal, but not cathodal tDCS specifically modulated intracortical inhibitory circuits, leading to a disinhibition. Significance: The results amplify our knowledge on excitability modulations of tDCS in stroke patients.